Healthy Living: Taking Care from Head to Toe - Jennifer Hillan; Emily Minton (EDIS)
If you have diabetes, pay special attention to your skin, eyes, teeth, gums, and feet. These areas are at increased risk for complications due to your diabetes. Read this revised 2-page fact sheet to learn how you can take care of your body from head to toe! Written by Jennifer Hillan and Emily Minton and published by the UF Department of Family Youth and Community Sciences, February 2011.